2013
DOI: 10.1517/13543784.2013.761972
|View full text |Cite
|
Sign up to set email alerts
|

Investigational therapies targeting the ErbB (EGFR, HER2, HER3, HER4) family in GI cancers

Abstract: Despite recent advances, the treatment of GI cancers remains challenging. Therapies targeting the HER family of receptors have been extensively studied in these malignancies with inconsistent results. The rationale behind varied tumor responses with these agents remains uncertain. We believe that additional studies are needed to identify biomarkers that could help identify a population of patients who would be more responsive to a given therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(26 citation statements)
references
References 105 publications
1
25
0
Order By: Relevance
“…EGF binding to cell membrane EGFR triggers EGFR conformational change to allow homodimerization with another EGFR or heterodimerization with another ErbB family and then induces receptor activation followed by subsequent receptor internalization to the early endosome. In the early endosome, EGFR is either recycled back to the cell surface or sorted to the late endosome/lysosome for degradation in termination of signal transduction [2628]. Several studies have shown that EGFR is capable of recruiting signaling molecules and transmit signals from endosome [2932], however, a recent study reports that EGFR signaling takes place primarily at the plasma membrane and the function of EGFR internalization is to terminate signals induced by EGF binding to plasma membrane EGFR [33].…”
Section: Discussionmentioning
confidence: 99%
“…EGF binding to cell membrane EGFR triggers EGFR conformational change to allow homodimerization with another EGFR or heterodimerization with another ErbB family and then induces receptor activation followed by subsequent receptor internalization to the early endosome. In the early endosome, EGFR is either recycled back to the cell surface or sorted to the late endosome/lysosome for degradation in termination of signal transduction [2628]. Several studies have shown that EGFR is capable of recruiting signaling molecules and transmit signals from endosome [2932], however, a recent study reports that EGFR signaling takes place primarily at the plasma membrane and the function of EGFR internalization is to terminate signals induced by EGF binding to plasma membrane EGFR [33].…”
Section: Discussionmentioning
confidence: 99%
“…The MAPK pathway, frequently upregulated in HCC [37], includes a cascade of phosphorylation of four major cellular kinases, Ras, Raf, mitogen-activated protein extracellular kinase (MEK), and extracellular signal-regulated kinase (ERK) [38]. …”
Section: Hepatocarcinogenesismentioning
confidence: 99%
“…ErbB2 receptor is a 175-kDa glycoprotein that lacks a known ligand and therefore relies on heterodimerization with other EGFR family members for signaling. Dimerization of ErbBs results in activation of multiple downstream signalling pathways such as the mitogenic Ras/Raf/extracellular-signal-regulated kinase 1/2 (ERK1/2), the p38 mitogen activated protein (MAP) kinase or the PI3-kinase/Akt survival pathways [7][10]. Alternatively, transactivation of ErbBs can occur via G-protein coupled receptors (GPCRs), such as angiotensin II (Ang II), thrombin, aldosterone and endothelin [11][15].…”
Section: Introductionmentioning
confidence: 99%